If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 = 2(u + -5) + -6u Reorder the terms: 10 = 2(-5 + u) + -6u 10 = (-5 * 2 + u * 2) + -6u 10 = (-10 + 2u) + -6u Combine like terms: 2u + -6u = -4u 10 = -10 + -4u Solving 10 = -10 + -4u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '4u' to each side of the equation. 10 + 4u = -10 + -4u + 4u Combine like terms: -4u + 4u = 0 10 + 4u = -10 + 0 10 + 4u = -10 Add '-10' to each side of the equation. 10 + -10 + 4u = -10 + -10 Combine like terms: 10 + -10 = 0 0 + 4u = -10 + -10 4u = -10 + -10 Combine like terms: -10 + -10 = -20 4u = -20 Divide each side by '4'. u = -5 Simplifying u = -5
| 1474x+4=20 | | 6000=(40+x)(x) | | 0.2(x+60)-0.08(x-30)=8.4 | | 12x+6=8x+42 | | 1/6x-2/7=4/7 | | f(x)=x^2+7x-7 | | (2x+1)(9x+b)=6x^2-5x+c | | 7.93-15.29v=0.66v | | 77=.5(7)(9+b) | | 6000=40w+w^2 | | 2(2c-3)-7=2c+5 | | a/4=32 | | 9x+1.5=19.5 | | -5w+4w^2+9=0 | | 6a-4ifa=7 | | 30-15x+6x=32+16 | | 4x+31=-x+1 | | 4-11=3 | | (4x^2-32x-26)/(x-9) | | 2=-3d+14 | | 3+8x=-3(-1-7x) | | -15=c/9-10 | | k=25+10x | | (7-z)(3z-8)=0 | | 48x^2-x-15=0 | | 2(x+4)+6=50 | | -5(-3p+3)=8(6p-6) | | (3x-7)(4x+4)=0 | | 0.3=x(1+x) | | 88=2(6p+8) | | -2(y-6)+1=0 | | X(y+5)=66 |